2021
DOI: 10.1093/gji/ggab236
|View full text |Cite
|
Sign up to set email alerts
|

Using magnetic techniques to calibrate hydrocarbon migration in petroleum systems modelling: A Case Study from the Lower Tertiary, UK Central North Sea

Abstract: Summary Magnetic minerals form or alter in the presence of hydrocarbons, making them a potential magnetic proxy for identifying hydrocarbon migration pathways. In this paper we test this idea by magnetically measuring core samples from the Tay Fan in the Western Central Graben in the Central North Sea. In a companion paper, 3D petroleum systems modelling has been carried out to forward model migration pathways within the Tay Fan. Rock magnetic experiments identified a range of magnetite, maghemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(26 citation statements)
references
References 50 publications
5
21
0
Order By: Relevance
“…The unaltered samples present with Curie temperature of ~580 °C suggesting the presence of original magnetite. Similar signatures have been observed in oil leg core samples from the Gannet and Guillemot fields, UK Central North Sea (Badejo et al, 2021c).…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…The unaltered samples present with Curie temperature of ~580 °C suggesting the presence of original magnetite. Similar signatures have been observed in oil leg core samples from the Gannet and Guillemot fields, UK Central North Sea (Badejo et al, 2021c).…”
Section: Resultssupporting
confidence: 79%
“…The geochemical requirements for the formation of lepidocrocite include a near neutral pH, a non-sulphidic environment and the presence of available iron (Gendler et al, 2005;Roberts, 2015). In a sulphidic environment, iron sulphide(s) will preferentially precipitate (Burton et al, 1993;Roberts, 2015;Badejo et al, 2021c). This likely accounts for the dominance of lepidocrocite at the OWTZ of the Bittern sands and its diminishing signature in the Pict and Bonneville sands.…”
Section: Formation Of Lepidocrocitementioning
confidence: 99%
“…Abubakar et al (2020) found a correlation between strongly magnetic samples and oil-stained samples, while unstained samples were more weakly magnetic. Mineral magnetic techniques have been used to identify hydrocarbon migration pathways and hydrocarbon contamination in soils and sediments (Badejo et al, 2021;Rijal, Porsch, Appel, & Kappler, 2012). Similarly, Gadirov, Eppelbaum, Kuderavets, Menshov, and Gadirov (2018) successfully identified hydrocarbon deposits from magnetic anomalies.…”
Section: Accepted Articlementioning
confidence: 99%
“…Temperatures as low as 50°C are sufficient to form new magnetic minerals (Kars et al, 2012). Hydrocarbon generation deeper in the sediment (e.g., Abubakar et al, 2015;Badejo et al, 2021;Elmore et al, 1987;McCabe et al, 1987) and tectonic fluid circulation (e.g., Elmore et al, 2001;McCabe et al, 1989) can lead to abiotic magnetic mineral formation and/or to alteration of pre-existing magnetic minerals. Rock-Eval pyrolysis measurements were carried out to further investigate potential effects of progressive increases in temperature, magnetic mineral content, and catagenesis (high temperature organic matter decomposition).…”
Section: Role Of Burial Temperature and Fluidsmentioning
confidence: 99%